Cholesteryl Phosphocholine – A Study on Its Interactions with Ceramides and Other Membrane Lipids - Lönnfors, Max; Långvik, Otto; Björkbom, Anders; Slotte, J.Peter (Langmuir, 2013)
We prepared cholesteryl phosphocholine (CholPC) by chemical synthesis and studied its interactions with small (ceramide and cholesterol) and large headgroup (sphingomyelin (SM) and phosphatidylcholine) colipids in bilayer membranes. We established that CholPC could form bilayers (giant uni- and multilamellar vesicles, as well as extruded large unilamellar vesicles) with both ceramides and cholesterol (initial molar ratio 1:1). The extruded bilayers appeared to be fluid, although highly ordered, even when the ceramide had an N-linked palmitoyl acyl chain. In binary systems containing CholPC and either palmitoyl SM or 1,2-dipalmitoyl-sn-glycero-3-phospholine, CholPC markedly destabilized the gel phase of the respective large headgroup lipid. In 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) bilayers, CholPC was much less efficient than cholesterol in ordering the acyl chains. In complex bilayers containing POPC and cholesterol or palmitoyl ceramide, CholPC appeared to prefer interacting with the small headgroup lipids over POPC. When the degree of order in CholPC/PCer bilayers was compared to Chol/PSM bilayers, CholPC/PCer bilayers were more disordered (based on DPH anisotropy). This finding may result from different headgroup orientation and dynamics in CholPC and PSM. Our results overall can be understood if one takes into account the molecular shape of CholPC (large polar headgroup and modest size hydrophobic part) when interpreting molecular interactions between small and large headgroup colipids. The results are also consistent with the proposed umbrella model” for explaining cholesterol/colipid interactions.